Curative in vivo hematopoietic stem cell gene therapy of murine thalassemia using large regulatory elements - Wang, Hongjie (JCI Insight, 2020)
Recently, we demonstrated that hematopoietic stem/progenitor cell (HSPC) mobilization followed by intravenous injection of integrating, helper-dependent adenovirus HDAd5/35++ vectors resulted in efficient transduction of long-term repopulating cells and disease amelioration in mouse models after in vivo selection of transduced HSPCs. Acute innate toxicity associated with HDAd5/35++ injection was controlled by appropriate prophylaxis, making this approach feasible for clinical translation. Our ultimate goal is to use this technically simple in vivo HSPC transduction approach for gene therapy of thalassemia major or sickle cell disease. A cure of these diseases requires high expression levels of the therapeutic protein (γ- or β-globin), which is difficult to achieve with lentivirus vectors because of their genome size limitation not allowing larger regulatory elements to be accommodated. Here, we capitalized on the 35 kb insert capacity of HDAd5/35++ vectors to demonstrate that transcriptional regulatory regions of the β-globin locus with a total length of 29 kb can efficiently be transferred into HSPCs. The in vivo HSPC transduction resulted in stable γ-globin levels in erythroid cells that conferred a complete cure of murine thalassemia intermedia. Notably, this was achieved with a minimal in vivo HSPC selection regimen.